Method development of ramipril and atorvastatin calcium capsule by using simultaneous equation method and absorbance ratio method - Rajawat, Prof. J. S. (Asian Journal of Pharmaceutics (AJP), 2014)
Ramipril is an angiotensinâ€converting enzyme inhibitor and atorvastatin calcium is inhibitor of 3â€hydroxyâ€3â€Â methylglutarylâ€CoA reductase used in the treatment of hypertension. Simple, precise, rapid and selective simultaneousÂ equation and Qâ€analysis methods have been developed for the simultaneous determination of ramipril and atorvastatin fromcombined capsule dosageforms.The methods involve solving of simultaneous equations and Qâ€value analysis based on measurementabsorptivity at 210.030 and 246.828 nm, respectively. Linearity lies between 2 and 25 mcg/ml for both drugs. Key words: Absorbance ratio method, atorvastatin, ramipril, simultaneous equation